O IRDR Nº 40/2016, DO COLEGIADO RECURSAL DO E. SANTO (DESASTRE DO RIO DOCE) E O DEVIDO PROCESSO LEGAL - Karninke, Tatiana Mascarenhas (2020)
The dissertation had as its object the case study embodied in IRDR nº 40/2016, triggered within the scope of the Special Civil Courts of Espirito Santo, known as the Samarco Case , here called Rio Doce Disaster . This IRDR was raised by letter by the Ju